2018
DOI: 10.2174/1566524018666180316150936
|View full text |Cite
|
Sign up to set email alerts
|

ROCK Inhibitor Y-27632 Promotes Human Retinal Pigment Epithelium Survival by Altering Cellular Biomechanical Properties

Abstract: Purpose: Dysfunction or death of retinal pigment epithelial (RPE) cells is a common pathogenesis of various types of retinal degenerative diseases. Recent reports indicated that ROCK pathway inhibitors regulate cell proliferation or apoptosis in a cell-type-dependent manner. Here, we aim to investigate the effect of ROCK inhibitor Y-27632 on the human retinal pigment epithelium (RPE) in vitro.Methods: Cell proliferation and apoptosis were analyzed by CCK-8 and flow cytometry respectively. Cell proliferation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…For example, intravitreally injected fasudil reduced retinal hypoxia and RPE barrier breakdown in Goto Kakizaki type 2 diabetic rats [69]. Ni et al investigating the effect of a ROCK inhibitor (Y-27632) on ARPE19 cells, observed increased proliferation and reduced apoptosis of RPE cells [70]. In our study, ARPE19 cells appeared unaffected by treatment with free and released fasudil.…”
Section: Discussionsupporting
confidence: 47%
“…For example, intravitreally injected fasudil reduced retinal hypoxia and RPE barrier breakdown in Goto Kakizaki type 2 diabetic rats [69]. Ni et al investigating the effect of a ROCK inhibitor (Y-27632) on ARPE19 cells, observed increased proliferation and reduced apoptosis of RPE cells [70]. In our study, ARPE19 cells appeared unaffected by treatment with free and released fasudil.…”
Section: Discussionsupporting
confidence: 47%
“…We found that the CR cell’s cytoskeleton appeared elongated with no difference in cell membrane height nor any immediate difference in the appearance of goblet cells or cilia from cross-sectional images. Previously, ROCK inhibitor has been shown to alter the biochemical properties of a cell by influencing the reorganization of cytoskeletal microfilaments and microtubules in retinal pigment epithelium ( 27 ). Future detailed studies of the cell cytoskeleton are warranted in CR cells before their use to answer research questions where cytoskeletal arrangements may be critical.…”
Section: Discussionmentioning
confidence: 99%
“…The PDMS-based culture device, which had a 0.2-mm curvature radius, was able to provide appropriate physical conditions for the formation and harvesting of RPE strips in a straightforward manner. The addition of Y-27632 generally suppresses contractility 15 and elongates the shape of human RPE 16 . In this study, the microgroove appeared to define the direction of cell elongation, resulting in shrinkage of the strip at a higher concentration of Y-27632, as a synergistic effect between physical and pharmacological conditions.…”
Section: Discussionmentioning
confidence: 95%